Aktualisasi Jadwal Salat Sepanjang Masa Abu Muhammad Isa Mulieng Aceh - Ismail Ismail Ismail; Husnaini Husnaini (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2021)
This paper aims to explain the actualization of one of the prayer schedules that are still guided by the people of Aceh. Prayer schedules circulating in the community are of various types and forms, patterns of preparation and accuracy also vary. This type of research uses a qualitative approach with the documentation method as a data collection technique The all-time prayer schedule of Abu Muhammad Isa work compiled in 1984 was very contemporary in his time and included in the type of conversion prayer schedule for the surrounding area and guided by the West Indonesia Time zone 105 ° (GMT + 7) in accordance with the Indonesian Presidential Decree. No. 243 of 1963. When compared with the results of the computational calculation, the prayer schedule is slower around 2 minutes than it should. This prayer schedule can be guided within a radius of 55.4 kilometers from the point of calculation, because it uses the value of ihktiyat 2 minutes and can still be used for all time because until now the resulting difference is only in seconds.